Sizing an open-channel woodchip bioreactor to treat nitrate from agricultural tile drainage and achieve water quality targets. Issue 3 (4th January 2022) - Krone, Pam; Clark, Ross; Adelaars, Jason; Leandro, Mason; Henson, Alex; Williamson, Jessica; Bischel, Heather; Wrightwood, Olivia; Watson, Fred
Abstract: Woodchip bioreactors are capable of removing nitrate from agricultural runoff and subsurface tile drain water, alleviating human health hazards and harmful discharge to the environment. Water pumped from agricultural tile drain sumps to nearby ditches or channels could be cost-effectively diverted through a woodchip bioreactor to remove nitrate prior to discharge into local waterways. Sizing the bioreactor to achieve targeted outlet concentrations within a minimum footprint is important to minimizing cost. Determining the necessary bioreactor size should involve a hydrological component as well as reaction type and rates. We measured inflow and outflow nitrate concentrations in a pumped open-channel woodchip bioreactor over a 13-month period and used a tanks-in-series approach to model hydrology and estimate parameter values for reaction kinetics. Both zero-order and first-order reaction kinetics incorporating the Arrhenius equation for temperature dependence were modeled. The zero-order model fit the data better. The rate coefficients (k = 17.5 g N m −3 day −1 and theta = 1.12 against Tref = 20 °C) can be used for estimating the size of a woodchip bioreactor to treat nitrate in agricultural runoff from farm blocks on California's central coast. We present an Excel model for our tanks-in-series hydrology to aid in estimating bioreactor size. HIGHLIGHTS: A tanks-in-series model is simple and can be used to depict hydrology and nitrate decay in woodchip bioreactors. Zero order kinetics better depicts nitrate decay rate than first-order kinetics for agricultural runoff. One can estimate the minimum size needed for a pumped tile-drain woodchip bioreactor to meet water quality objectives using an Excel model.